Professionalism, stigma, and willingness to provide patient-centered safe abortion counseling and care: a mixed methods study of Ethiopian midwives - Addisu Fekadu; Aster Berhe; Belete Belgu; Ibrahim Yimer; Yeshitila Tesfaye; Sarah Jane Holcombe; Sahai Burrowes (BMC, 2022)
Plain Language Summary When health care workers refuse to provide safe abortion care (SAC) for religious, moral, or personal reasons, they jeopardize their clients' health and violate the right to care. Scholars believe that health care workers' professional commitments to patient care and to their profession's goals can help them prioritize patient care over their personal biases. The Ethiopian government has assigned midwives a central responsibility to provide SAC, but there is no comprehensive understanding of Ethiopian midwives' willingness to provide SAC and allied rationales, or the relationships between their sense of professional duty and willingness to provide. To answer these questions, a survey and focus groups with midwives in Ethiopia's five most populated regions were conducted. Almost half of midwives were unwilling to provide SAC, and half disbelieved that it was midwives' duty to do so. Most believed that midwives should be able to refuse to provide SAC based on religious or moral objections. Midwives were motivated to provide care by a belief that clients would die without care and by a sense of professional duty. When asked about how they would treat women requesting abortion care and contraceptives, many midwives said that they would encourage the woman to do what the midwife him- or herself thought best, rather than support her in making her own decision. These regionally representative findings suggest the need for new provider guidelines to clarify practices surrounding conscientious objection and refusal to provide safe abortion care and for programs to better train midwives to provide respectful counseling.